The relationship between oral and written narratives: A three‐year longitudinal study of narrative cohesion, coherence, and structure. (16th September 2015) - Pinto, Giuliana; Tarchi, Christian; Bigozzi, Lucia
Abstract : Background: The relationship between oral language and the writing process at early acquisition stages and the ways the former can enhance or limit the latter has not been researched extensively. Aims: The predictive relationship between kindergarten oral narrative competence and the first‐ and second‐grade written narrative competence was explored in a 3‐year longitudinal study. Among the first and second graders, the relationship between orthographic competence and narrative competence in written productions was also analysed. Sample: One hundred and nine Italian children participated in this study. Measures: Kindergarteners produced an oral narrative, whereas the first and second graders produced a written narrative. The oral and written narratives were analysed in terms of cohesion, coherence, and structure. The first‐grade orthographic competence was assessed via a dictation task. Results: Multiple linear regression and mediational analyses were performed. Kindergarten oral narrative competence affected the first‐ and second‐grade written narrative competence via a mediational effect of orthographic competence. Conclusion: The results suggest the importance of practicing oral narrative competence in kindergarten and first grade and the value of composition quality independent of orthographic text accuracy.